How Capital Goods Firms Upgrade Innovation Capacity : A Case Study - Erman Aminullah; Dian Prihadyanti; Irene Muflikh Nadhiroh; Chichi Shintia Laksani (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2014)
Objective of the research is to reveal how networks upgrade innovation capacity and to derive policy suggestions necessary for enhancing capa-bilities for process improvements and innovations, including interactions between users and producers in capital goods industry. The case study results showed that: i) the main driver of technological learning in the capital goods companies is the vision of top management; ii) product innovation as the improvement of existing product can be the results of informal learning without doing formal R&D activity; iii) the limited co-operative arrangements among producer, supplier and consultant are sufficient for stimulating lower level of innovations, which is 'new to the firma' innovations - rather than 'new to the market'; and iv) the pro-ducers-users interaction in the forms of exchange in goods and information as well as cooperation will contribute to stimulate innovation in companies. Knowledge sharing through innovation network has a central role in upgrading innovation capacity. It implies that the necessary poli-cies to intensify the wiring innovation network in capital goods industry are: i) the establishment of bridging institution or network broker for training, facilitating and mobilizing of network formation; ii) government financial assistance for hiring external experts/consultant to upgrade the innovation capacity of industry; iii) incentives (i.e.financial compensa-tion, recognition and career advancement) for university and research institute professors working to upgrade the innovation capacity of indus-try; and iv) government consultancy services and/or subsidized consul-tancy services from universities/research institutions to upgrade innovation capacity of industry.